Diagnostic Accuracy and Interobserver Agreement of p53 Immunohistochemistry in Endometrial Carcinoma: Correlation with TP53 Mutation by Next-Generation Sequencing - Lertsatit, Anchaleerat; Chamninawakul, Padol; Shuangshoti, Somruetai; Pongsuvareeyakul, Tip; Pohthipornthawat, Natkrita; Khunamornpong, Surapan; Teerapakpinyo, Chinachote; Shuangshoti, Shanop (Journal of Health Science of Thailand, 2025)
p53 immunohistochemistry (IHC) serves as a surrogate marker for TP53 mutation in endometrial carcinoma, but its diagnostic performance requires validation against next-generation sequencing (NGS). This retrospective study evaluated diagnostic accuracy and interobserver agreement of p53 IHC compared with TP53 mutation status in 60 endometrial carcinoma cases (2020-2022) from the Institute of Pathology, Ministry of Public Health, Thailand. Formalin-fixed, paraffin-embedded tissues with WHO-confirmed diagnosis underwent TP53 mutation analysis using targeted NGS (oncomine panel) and p53 IHC (clone DO-7). The resulting IHC slides were then independently interpreted by three blinded pathologists. TP53 mutations were detected in 12/60 cases (20%) by NGS; p53 IHC correctly identified 7/12 mutation-positive and 47/48 wild-type cases, yielding sensitivity of 58.33% (95%CI: 28.6-83.5), specificity of 97.92% (95%CI: 88.9-99.9), positive predictive value of 87.50% (95%CI: 46.7-99.3), and negative predictive value of 90.38% (95%CI: 78.696.5). Interobserver agreement was substantial (Fleiss’ kappa = 0.71, 95%CI: 0.62-0.80) among the 51 cases deemed interpretable by all pathologists. Notably, all eight abnormal cases achieved perfect consensus, while all disagreements occurred within wild-type patterns. We conclude that p53 IHC represents a reliable rule-in test given its high specificity and substantial reproducibility; however, its moderate sensitivity necessitates confirmatory molecular testing for wild-type or ambiguous staining.